“ANALISIS MATERI BUKU SUPER DEUTSCH LEKTION 4 “DIE KLASSENFAHRT: EINE UNVERGESSLICHE” DENGAN GER DAN PROFILE DEUTCSH” - Maharani, Yesika; Siagian, Natasya Engel; Siregar, Hana Gloria (Cahaya Ilmu Bangsa Institute, 2025)
The Super Deutsch book is a German language learning reference designed according to the Common European Framework of Reference for Languages (CEFR). Lesson 4, titled